PELATIHAN DASAR AUDIT DENGAN MICROSOFT EXCEL BAGI SISWA SMA KRISTEN YUSUF - Imelda, Elsa; Yola; Nanang, Sheila Elita (Jurnal Serina Abdimas, 2024)
In the increasingly advanced digital era, technology skills are becoming increasingly important in various aspects of professional and personal life. One skill that remains relevant and highly valuable is Microsoft Excel. Microsoft Excel has developed features and has many functions. Various activities can be carried out with Microsoft Excel. For example, data management, data analysis, mathematical calculations, making budgets, making tables, graphs, sorting data and even accounting software for making financial reports. And it cannot be separated from the fact that Microsoft Excel can help in the audit field. Microsoft Excel not only increases individual efficiency and productivity, but also has a significant impact on the future. So the ability to apply Excel becomes an asset for adapting to society, both for doing assignments as a student and helping with work in the industrial world. SMA Kristen Yusuf students take information technology subjects and have mastered Microsoft Excel. They also often do assignments using Excel. However, they don't understand how Excel can help work in the industrial world. This problem was assisted by the Untar PKM team to train the use of Excel in the audit field and the audit level was at the basic level. The PKM team provides initial training on auditing, then training on how to audit using Microsoft Excel. The Microsoft Excel features taught include sampling, auto filtering, data tagging, and using basic commands that are useful for auditing. Students feel the additional knowledge is useful ABSTRAK Pada era digital yang semakin maju, keterampilan teknologi menjadi semakin penting dalam berbagai aspek kehidupan profesional dan pribadi. Salah satu keterampilan yang tetap relevan dan sangat berharga adalah Microsoft Excel. Microsoft Excel telah berkembang fiturnya dan memiliki banyak fungsi. Berbagai kegiatan dapat dilakukan dengan Microsoft Excel. Misalnya manajemen data, analisis data, perhitungan matematika, membuat anggaran, membuat tabel, grafik, mengurutkan data bahkan sebagai software Akuntansi dalam membuat laporan keuangan. Dan tak lepas juga ternyata Microsoft Excel dapat membantu dalam bidang Audit. Microsoft Excel tidak hanya meningkatkan efisiensi dan produktivitas individu, tetapi juga memiliki dampak yang signifikan di masa depan. Sehingga kemampuan mengaplikasikan Excel menjadi satu modal untuk beradaptasi di masyarakat, baik untuk mengerjakan tugas sebagai pelajar hingga membantu pekerjaan di dunia industri. Siswa/i SMA Kristen Yusuf mendapatkan mata pelajaran teknologi informasi dan sudah menguasai Microsoft Excel. Mereka juga sering mengerjakan tugas dengan memakai bantuan Excel. Namun mereka belum paham bagaimana Excel dapat membantu pekerjaan di dunia industri. Masalah ini dibantu oleh tim PKM Untar untuk melatih penggunaan Excel di bidang audit dan level auditnya di level dasar. Tim PKM memberikan pelatihan awal mengenai audit, kemudian pelatihan cara mengaudit dengan menggunakan Microsoft Excel. Fitur Microsoft Excel yang diajarkan berupa pengambilan sampel, auto filter, penandaan data, dan pemakaian perintah dasar yang bermanfaat bagi audit. Siswa merasakan ilmu tambahan yang bermanfaat.